Development of 3-Dimensional Model of Femur Bone Considering Cortical and Cancellous Structures - Mohd Amir Shahlan, Mohd Aspar; Nasrul Anuar, Abd Razak; Mohammed Rafiq, Abdul Kadir; Hadi, Manap (Penerbit Universiti Malaysia Pahang, 2017)
Femur bone is commonly used for various experimental and computer simulation works in multidiscipline research. Various techniques are applied prior to mimic the actual bone properties. In order to perform any research related to human bone, some issues need to take into account such as cost, ethical concern and limited bone sample availability. Experimental test and computer simulation related to femur bone model commonly executed using hollow cylinder, solid rod or beam elements instead of real anatomy. The aims of present study is to provide 3D femur bone model construction considering both cortical and cancellous structures utilising only one software approach. The constructed model could be utilised for various research purposes such as computer simulation, 3D print of bone model and experimental test. Complete femur bone model which include proximal, shaft and distal condyles is successfully constructed and ready to be used for further investigation. Mimics software was the only software used in present study to performed overall task